2020
DOI: 10.1016/j.meatsci.2019.108035
|View full text |Cite
|
Sign up to set email alerts
|

Carnobacterium maltaromaticum as bioprotective culture in vitro and in cooked ham

Abstract: The bioprotective effects of Carnobacterium maltaromaticum (CM) strains were assessed in vitro and in sliced cooked ham. CM strains were tested in vitro against Listeria monocytogenes (LM), Escherichia coli O157:H7 (EC) and Salmonella Typhimurium (ST). In vitro effect was evaluated using co-culture (with and without EDTA) and cell-free supernatant (CFS). CFS was tested by agar well diffusion and minimum inhibitory concentration. In cooked ham, the inhibitory effect of CM on L. innocua (LI) and on the physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In vitro studies have demonstrated the ability of Carnobacteriaceae, a group of bacteriocin producing lactic acid bacteria to reduce the virulence of Listeria monocytogenes on colonic epithelial cells. 78 Further, members of Carnobacteriaceae were proven to be effective as a probiotic in food-animal production 79 , 80 , 81 suggesting that they may exert a similar effect on the oral epithelial barrier. Furthermore, members of the family Bifidobacteriaceae are part of the oral commensal bacteria known to exert beneficial effects in the oral cavity and are currently being used as probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated the ability of Carnobacteriaceae, a group of bacteriocin producing lactic acid bacteria to reduce the virulence of Listeria monocytogenes on colonic epithelial cells. 78 Further, members of Carnobacteriaceae were proven to be effective as a probiotic in food-animal production 79 , 80 , 81 suggesting that they may exert a similar effect on the oral epithelial barrier. Furthermore, members of the family Bifidobacteriaceae are part of the oral commensal bacteria known to exert beneficial effects in the oral cavity and are currently being used as probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This may consist of the assumption of the Jameson effect that the dominating microbiota quantitatively inhibits growth of the pathogen in the same way that they inhibit their own growth, and the pathogen therefore stops growing at the time when the dominating microbiota reach their maximum population density. Other studies also find the same phenomenon, whether the original beef microflora consisted mainly of LAB of which approximately 80% were L. sakei (Vold et al, 2000 ) or a single strain with bacteriostatic properties (Danielski et al, 2020 ) was used as a high‐concentration microbial background, its effective prevention and control of pathogenic microorganisms in overwrapped packaging was confirmed. Other reports also confirmed that high concentrations of microflora in raw meat inhibited the growth of Salmonella spp.…”
Section: Resultsmentioning
confidence: 67%
“…This result agrees with the findings of Castellano et al ( 2011 ), who found that after treatment with L. curvatus CRL705 and Lactococcus lactis CRL1109, the pH value of beef steaks did not change significantly over 9 days of storage. Another study conducted by Danielski et al ( 2020 ) also reported that over 7 days after the ham surface was inoculated with C. maltaromaticum , no significant changes in pH value were found. However, a study reported that after a storage period of 38 days under vacuum conditions, L. sakei and L. curvatus significantly reduced the pH of fresh beef to 5.27 and 5.34, respectively (Zhang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations